2020
DOI: 10.7759/cureus.10282
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Substance Use in Acute Injuries With Regards to the Intent, Nature and Context of Injury: A CHIRPP Database Study

Abstract: Michaud-Germain et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…Prior to the suicide attempt, visits were primarily for behavioral health or substance abuse problems in the ED [25]. Interventions that consider the unique characteristics of older adults, such as the burden of chronic and debilitating physical injuries, might be more useful than general interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the suicide attempt, visits were primarily for behavioral health or substance abuse problems in the ED [25]. Interventions that consider the unique characteristics of older adults, such as the burden of chronic and debilitating physical injuries, might be more useful than general interventions.…”
Section: Discussionmentioning
confidence: 99%
“…16 17 Additionally, an investigation of the Canadian Hospitals Injury Reporting and Prevention Program found that alcohol and drug use were more frequently associated with intentional injuries compared with unintentional injuries; the investigation also found that trauma survivors presenting with alcohol and drug use were more likely to be younger and male. 18 Literature review revealed few trauma center-based investigations that have assessed the association between PTSD and alcohol and drug use comorbidities in injured patients. One prior investigation at a single level I trauma center found that among 878 randomly sampled hospitalized injury survivors, approximately 80% presented with either elevated PTSD symptom levels and/or alcohol, opioid, stimulant, and marijuana comorbidities.…”
Section: Open Accessmentioning
confidence: 99%
“…Other single-site investigations have found that trauma survivors of younger age, Caucasian race and male sex were more likely to be suffering from alcohol and drug use comorbidity 16 17. Additionally, an investigation of the Canadian Hospitals Injury Reporting and Prevention Program found that alcohol and drug use were more frequently associated with intentional injuries compared with unintentional injuries; the investigation also found that trauma survivors presenting with alcohol and drug use were more likely to be younger and male 18…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that traumatic injuries are often associated with substance abuse [8][9][10]; however, the patterns of substance abuse and the associated trauma mechanism have not been fully understood. The emergency department (ED) has evolved into the de facto treatment site for substance abuse presentations; it can serve as public health surveillance resource for substance abuse and traumatic injuries.…”
Section: Introductionmentioning
confidence: 99%